Pembuatan dan Sosialisasi Absensi Digital Berbasis Barcode di SMP N 2 Suwawa - Hermila A.; La Ode Gusman Nasiru; Indra Farman; Haikal Bahri; Seftiani Wulandari A.M. Nay; Nizahrawaty Saleh; Putri Sesiliya Mohamad (Universitas Negeri Gorontalo, 2026)
This community service activity aimed to design, implement, and socialize a barcode-based digital attendance system to improve the efficiency of student attendance management at SMP Negeri 2 Suwawa. The activity was carried out through observation, interviews, needs analysis, system design, system testing, training, and implementation by utilizing Google Forms and Google Spreadsheets as the attendance database platform. Before the program, student attendance was recorded manually, resulting in time-consuming data recapitulation and a higher risk of recording errors. The implementation results demonstrate that the developed system successfully enables automatic attendance recording through barcode scanning, provides real-time attendance monitoring, and simplifies monthly attendance recapitulation for teachers. In addition, the activity improved teachers' understanding of the use of digital technology in attendance management and supported the school's digital transformation initiatives. Therefore, the barcode-based digital attendance system provides a practical, efficient, and sustainable solution for managing attendance in schools.